Dimensions and directions of how to live - جوان اسماعیل بكر; دانا لطیف جالل (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
Our aim of this research is to share the goals and orientations of different qualities of life, that forms the basis for realizing the Social Sciences. Highlighted on this goal has been asking the question the main research agencies: do the goals and directions of the quality of life have any key roles in the configuration of the theoretical understanding in this subject? Because of the quality of life in social science is significant, this research has a major role in understanding and exploring its directions and theories, and this research can review the qualities of life as theoretical analysis. Since the quality of life is such a major issue and is directly connected to public health, mental state, independence rate, social relations, individual beliefs, and its social environment. And orientations of the qualities of life vary. If the previous researches have always been one-way, now in our own time, this trend no longer has this special attention, to the point it has become a part of the guidance for a better life.